Dynamical behavior of the bright incoherent spatial solitons in self-defocusing nonlinear media. (April 2016) - Zhang, M.; Huo, G.; Duan, Z.
Abstract: We present a theory of bright incoherent photovoltaic (PV) solitons in self-defocusing nonlinear media by using a coherent density approach. It is shown that this theory model is effectively governed by an infinite set of coupled nonlinear Schrödinger equations, which are initially weighted with respect to the incoherent angular power spectrum of source. We then numerically study the particular case of spatially incoherent beam propagating in LiNbO3 :Fe crystal with split-step Fourier method. Numerical simulations indicate that the ratio of PV constant κ is a key parameter to spatial compression as well as the possible dark and bright PV solitons. Besides, the formation of bright incoherent PV solitons is affected by intensity ratios rT and width of the source angular power spectrum θ 0 . Better coherent property is found at margins of bright incoherent soliton through the associated coherence length calculation. These results are in good agreement with recent experimental observations.